Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial Rural de Timbara, Provincia de Zamora Chinchipe, periodo Enero – Diciembre 2020 - Quezada Quezada, Erika Lizbeth (2023)
The curricular integration work called AUDITORÍA FINANCIERA AL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL RURAL DE TIMBARA, PROVINCIA DE ZAMORA CHINCHIPE, PERIODO ENERO – DICIEMBRE 2020, was done as a prerequisite to obtain the degree of Bachelor in Accounting and Auditing, developed according to the Academic Regulations of the National University of Loja. In the curricular integration work, the proposed objectives were met, such as evaluating the internal control system implemented by the entity, to determine the reasonableness of the balances presented in the Financial Statements; verify compliance with constitutional, legal, regulatory and normative provisions and prepare the report of results obtained, along with conclusions and recommendations, in order to improve the management of financial resources. Therefore, to measure the effectiveness of the internal control system maintained by the entity, the questionnaire method was applied to determine the weak points of each component examined, and to observe the degree of compliance with the regulations in force, with the purpose of contributing to the improvement and strengthening of the administrative management. Proceeding with the review of the supporting documentation that justifies the administrative and financial operations related to the audited components; in order to evaluate the management of available funds, review the obligations contracted with third parties; The movement of the main audited accounts and the reasonableness of the balances presented in the financial statements were verified through the application of auditing procedures set forth in analytical and summary reports; to determine the actual balance of the account and establish its reasonableness by comparing them with the entity's general ledgers. The methodology used in the financial audit consisted in the use of techniques such as observation to know the existing reality in the entity, the previous visit guide was applied to obtain institutional information, the application of the audit phases was carried out: Preliminary planning, in which the knowledge of the entity, its structure and its main activities shown in the preliminary risk matrix was made; specific planning, in which the strategy to be followed in the work was defined; then the execution was carried out, where the evaluation of internal control, audit programs and procedures was carried out; Finally, in the phase of communication of results, which is considered as the final part of the financial audit, an audit report was presented containing comments, conclusions and recommendations, which summarizes all the information found in the working papers and is presented as a synthesis for the knowledge and consideration of the officers of the entity.